Increased Socioeconomic Impacts With Future Intensifying Flash Droughts in China - Yuchen Li; Yuyue Xu; Jiangling Liao; Junzheng Pi; Wenfeng Zhan; Jianli Chen; Ling Yao; Chenghu Zhou (Geophysical Research Letters)
Abstract Amid global warming and rapid urbanization, China faces the challenge of an increasing frequency and severity of flash droughts. However, the impact of flash droughts on the socioeconomic conditions has not been sufficiently explored. Here, we elucidate the evolutionary characteristics of flash droughts in China and project future trends in their impacts on socioeconomic conditions under different climate scenarios by analyzing soil moisture and socioeconomic data. We estimate that the frequency of flash droughts is projected to increase in specific regions of China, along with an increasingly substantial socioeconomic impact over time. Under SSP2‐4.5, the population and gross domestic product exposed to flash droughts are anticipated to reach 33% and 35% by the end of this century, respectively. Furthermore, richer subgroups face higher economic risks and greater social vulnerability. These findings may help policymakers assess the adverse effects of flash droughts and formulate policies to mitigate the threats to sustainability.